Knowledge and perception in implementing principle 1-4 of MSPO among independent smallholder case of Sungai Rambai, Melaka / Che Nurul Azwin Che Mohd Nordin and Firdaus Aziz - Che Mohd Nordin, Che Nurul Azwin; Aziz, Firdaus (Faculty of Plantation and Agrotechnology, 2018)
The oil palm plantations in Malaysia are largely based on the estate management system and smallholder scheme. The area planted was increasing rapidly from 1.8 million hectares in 1985 becoming a 5.81 million hectare in 2017. However, independent smallholders has possessed a major threat towards Malaysia such as lacking in term of documentation preparation, awareness and higher in cost implementation. Thus, it is perceive that this sector is unproductive and inefficient as compared to the large-scale production system of the estate sector as they are tend to not achieved the standard principle in existing sustainability standard. In this study, researcher are decided to study about knowledge and perception of Principle 1-4 Malaysian Sustainable Oil Palm (MSPO) among independent smallholder in Malaysia. This study are conducted in Sungai Rambai. Melaka. The population size of this study is about 50 smallholders. For this study, the researcher needs only 44 samples to analyse based on Krejcie and Morgan table. The questionnaires will be use to collect data and the questionnaires will be distributed to the selected smallholders. Pearson correlation is use to analysed the relationship between independent and dependent variables which independent refer to knowledge and perceptions while the dependent variables is referring to principle 1-4 of MSPO. Finding of this study had shown there is a significant and non-significant relationship between the two variables that stated earlier. It proved that perception of independent smallholder are most dominant tov ard principle 1-4 of MSPO certification in Malaysia